Расчет основных параметров канатных амортизаторов; Строительные и дорожные машины; № 4 - Горбунов В. Ф. Валерий Федорович; Резников И. Г.; Козлов В. В.; Рудаченко А. В. Александр Валентинович (1975, 1975)
В фонде НТБ ТПУ отсутствует